Onset of polyarticular juvenile idiopathic arthritis with both anti-cyclic citrullinated peptide antibodies and rheumatoid factor in a 3-year-old girl - Yasui Kozo; Sakata Sonoko; Ochi Hideaki; Itamura Shinji; Hirai Kenta; Takenaka Mieko; Mitani Osamu; Ogawa Kazunori; Iyoda Kuniaki (Pediatric Rheumatology Online Journal, 2012)
Abstract This report describes 3 year old girl with the unusual presentation of polyarticular juvenile idiopathic arthritis (JIA) with anti-cyclic citrullinated peptide (anti-CCP) antibodies and a positive rheumatoid factor (RF). She was initially treated with a nonsteroidal anti-inflammatory drug (NSAID; ibuprofen) followed by methotrexate (MTX, 10 mg/m2/week) and prednisolone (0.25 mg/kg/day), but these treatments were ineffective. Administration of tocilizumab, a humanized antihuman interleukin-6 receptor monoclonal antibody, promptly improved her clinical manifestations, and she has been in complete remission (DAS28 <2.6) without bone erosion and/or destruction. Positivity for both antibodies (anti-CCP and RF) can forecast the severity of JIA (radiographic bone destruction). In such cases the administration of biologic remissive therapy may be prudent early in the disease course.